Systematized inflammatory linear verrucous epidermal nevus moderately responsive to systemic acitretin and topical calcipotriol - Sanjay Singh; Mamta Rai; Neetu Bhari; Savita Yadav (Indian Journal of Paediatric Dermatology, 2018)
Inflammatory linear verrucous epidermal nevus (ILVEN) is a rare form of epidermal nevus which usually presents in childhood, mostly on the lower half of the body in a blaschkoid distribution. A wide variety of topical, systemic, and surgical modalities have been tried for its treatment, but it is known to be refractory to treatment. We hereby are reporting a rare case of extensive systematized ILVEN which showed moderate response to treatment with acitretin and topical calcipotriol.